Implementing Project-Based Learning to Enhance Critical Thinking Skills in High School Students - Taufik Huda; Abdul Malik; Nurani Ai Erlinawati; Andhika Lungguh Perceka; Yance Manoppo (PT Inovasi Pratama Internasional, 2024)
The objective of this study is to ascertain student responses and enhance their critical thinking abilities through the implementation of project-based learning models at SMA 6 Jakarta. To achieve these objectives, this research was conducted using the qualitative method. This study focused on 19 students at SMA 6 Jakarta. It examined the application of a project-based learning model and related factors, including students' responses, their critical thinking abilities, implementation constraints, and efforts to address these issues. Data were gathered through a combination of methods, including observation, in-depth interviews, focus group discussions, document recording, questionnaires, and critical thinking tests. The resulting data were analyzed both quantitatively and qualitatively. The findings indicated that implementation of learning at SMA 6 Jakarta using a project-based learning model has led to notable improvements in students' critical thinking abilities. Additionally, the student response to the learning process was largely positive.